Micropropagación e inducción de órganos de almacenamiento en Curcuma longa L. (2011)
ABSTRACT: One of the important characteristics of the plant species Curcuma longa L. is its chemical composition that makes it commercially attractive, because in addition to its pigments, which are used as food dyes or in medicines, it contains acetones and alcohols that give avor to its rhizomes, making useful as a spice. Curcuma propagation is mainly conducted asexually, with low propagation rates; in addition, the rhizomes are susceptible to disease, making their storage dif cult. Plant tissue culture offers, among other alternatives, microrhizome production, facilitating management in the greenhouse and eld, transportation, exchange, and conservation. The goal of this project was to introduce and multiply C. longa plants in vitro, and induce microrhizome formation. After standardization of a disinfection protocol, the height and coef cient of multiplication of the established apexes were evaluated as response indeces to differing bencilaminopurine concentrations. Vitroplants of 10 cm were used to induce microrhizomes, and their formation, mean number, and morphological characteristics were evaluated. The results obtained suggested that MS medium with 2 mg/l bencilamonopurine (BAP) is adequate for producing a good quantity and quality of new plants. Conditions of total darkness and a sugar concentration above 60 g/l were key factors in the induction of microrhizomes.